Current Approach to Treatment for Central Serous Chorioretinopathy. Review - A. K. Drakon; L. S. Pateyuk; V. M. Sheludchenko; N. B. Korchazhkina (Oftalʹmologiâ)
Central serous chorioretinopathy (CSC) is a disease of complex origin and unknown etiology. Traditionally, two clinical forms of CSC are verified in accordance with the activity and duration of the pathological process: classic acute form and chronic CSC. Nowadays, there is no unified concept accepted for the management of patients with this disease, particular difficulties exist in cases of chronic CSC. This literature review highlights current trends and approaches to the treatment of CSC patients — from focal laser photocoagulation to physical methods oh therapy. The therapeutic approach as a whole depends on the form of the CHS. In most cases of the acute form of CSF, spontaneous regression, spontaneous adhesion of RPE detachment and retinal neuroepithelium are noted within several months from the onset of the disease. Therapy for the chronic form of this disease is still a difficult task and a controversial issue. Direct laser coagulation of the retina at the oozing point is recognized as the most effective method of therapy for acute typical form of CSF. In the chronic form of CSC, photodynamic therapy, transpupillary thermotherapy and subthreshold micropulse laser exposure are used. The goal of drug therapy for CSF is to activate the processes of resorption of serous fluid from the subretinal or subpigmented space, reduce the activity of pathological processes in the choroid, and improve trophism and metabolism. The currently used methods of treating chronic CSH have a number of disadvantages and variable efficacy. The existence of treatment-resistant cases is the subject of further research and clinical research. The development of new physical and physiopharmacological methods of treatment for CSF is perspective.